Calcium serum concentration among pregnant women in a tertiary hospital and its satellite hospital in Medan, Indonesia - Muhammad Agung Khoiri; Sarma N Lumbanraja; Duddy Aldiansyah; M. Fidel Ganis Siregar; Makmur Sitepu; M. Rhiza Tala (Universitas Airlangga, 2022)
HIGHLIGHTS 1. Serum calcium concentration in pregnant women who took prenatal appointments in the general hospital and its satellite hospitals were evaluated.2. It was found that serum calcium concentration in those pregnant women who made the prenatal appointments were normal. ABSTRACT Objectives: This study aimed to evaluate serum calcium concentration in pregnant women who made prenatal appointments to Obstetric and Gynecologic Outpatient Clinics at Adam Malik General Hospital, Medan, Indonesia, and its satellite hospitals. Materials and Methods: This study was a descriptive study with a case series approach. The case series of the study included 35 pregnant women in their second or third trimester chosen by consecutive sampling method. Results: The mean calcium serum level of pregnant women in the second and third trimester was 9.12±0.49 mg/dl and 8.97±0.26 mg/dl, respectively. The mean calcium level of pregnant women aged <20, 20-35, and >35 years old were 9.0±0.28 mg/dl, 9.07±0.44 mg/dl, and 8.96±0.06 mg/dl, respectively. Conclusion: This study found that the mean calcium serum level of pregnant women who took prenatal appointments in Haji Adam Malik General Hospital, Medan, Indonesia, was normal.